2016
DOI: 10.1002/jssc.201600611
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of polydopamine‐coated imprinted polymers on the surface of SiO2 for estrone capture in milk samples

Abstract: Estrone molecularly imprinted polymers were synthesized through the self-polymerization of dopamine on the surface of silica gels, which had the characteristics of mild polymerization conditions, simple reaction procedure and good specific recognition ability for estrone. The estrone molecularly imprinted polymers were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, elemental analysis and nitrogen adsorption-desorption tests. The characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Likewise, Zheng et al. observed that the silica gels showed a fairly smooth surface, and it was quite different from the surface of estrone molecularly imprinted polymers that had rough surfaces . TEM images (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Likewise, Zheng et al. observed that the silica gels showed a fairly smooth surface, and it was quite different from the surface of estrone molecularly imprinted polymers that had rough surfaces . TEM images (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Compared to functionalized silica particles, PSMIPs have a rough surface; this could be attributed to the polymerization process producing imprinted recognition sites on the surface of functionalized silica particles [30]. Likewise, Zheng et al observed that the silica gels showed a fairly smooth surface, and it was quite different from the surface of estrone molecularly imprinted polymers that had rough surfaces [31]. TEM images ( Fig.…”
Section: Stability and Reusability Of Psmipsmentioning
confidence: 97%
“…The calculated SC values for prednisolone acetate, estrone, diethylstilbestrol, and estradiol were 1.36, 1.44, 1.94, and 1.88, respectively. The difference suggested that the high selectivity was attributed to the complementary shape, size, spatial distribution, and molecular interactions of imprinting sites in MIPs cavities [25,35].…”
Section: Selectivitymentioning
confidence: 99%
“…In one work, Estrone, a steroid hormone responsible for organism maturation and feed additive for animal growth and lactation, was imprinted with DA for 12 h over silica gels. The resulted MIP was used successfully with linearity relationship in the range of 0.2–20 μg/mL in SPE–HPLC for estrone analysis in milk samples …”
Section: Protein Imprintingmentioning
confidence: 99%